2020
DOI: 10.1002/jbmr.3957
|View full text |Cite
|
Sign up to set email alerts
|

BMP9 Reduces Bone Loss in Ovariectomized Mice by Dual Regulation of Bone Remodeling

Abstract: Bone remodeling is dynamic and is tightly regulated through bone resorption dominated by osteoclasts and bone formation dominated by osteoblasts. Imbalances in this process can cause various pathological conditions, such as osteoporosis. Bone morphogenetic protein 9 (BMP9), a biomolecule produced and secreted by the liver, has many pharmacological effects, including anti-liver fibrosis, antitumor, anti-heart failure, and antidiabetic activities. However, the effects of BMP9 on the regulation of osteoblast and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 62 publications
(73 reference statements)
2
25
0
Order By: Relevance
“…(66) A recent study has demonstrated that LGR6 acts to potentiate Wnt/β-catenin signaling in MC3T3-E1 cells downstream of BMP signaling, leading to transcription of osteogenic genes. (67) LGR4 is expressed within BMSCs undergoing osteogenic differentiation; however, the expression levels of LGR4 do not appear to be correlated with osteogenic genes or in vitro osteoblastic differentiation of BMSCs. (65) Although LGR4 may not serve as a marker for osteoblast precursors in the same manner as LGR6, others have demonstrated a necessary role for LGR4 in osteogenic differentiation in vitro.…”
Section: Lgrs In Skeletal Remodelingmentioning
confidence: 89%
See 2 more Smart Citations
“…(66) A recent study has demonstrated that LGR6 acts to potentiate Wnt/β-catenin signaling in MC3T3-E1 cells downstream of BMP signaling, leading to transcription of osteogenic genes. (67) LGR4 is expressed within BMSCs undergoing osteogenic differentiation; however, the expression levels of LGR4 do not appear to be correlated with osteogenic genes or in vitro osteoblastic differentiation of BMSCs. (65) Although LGR4 may not serve as a marker for osteoblast precursors in the same manner as LGR6, others have demonstrated a necessary role for LGR4 in osteogenic differentiation in vitro.…”
Section: Lgrs In Skeletal Remodelingmentioning
confidence: 89%
“…Mouse Promotes osteogenesis via RSPO2 binding; becomes upregulated upon BMP2 exposure Luo et al (48) ; Zhu et al (68) ; Pawaputanon na Mahasarakham et al (71) ; Zhou et al (67) LGR4 Preosteoclasts, osteoclasts…”
Section: Lgrs In Skeletal Remodelingmentioning
confidence: 99%
See 1 more Smart Citation
“…The method of ALP and TRAP staining were similar as performed before. The osteoblast surface/bone surface (Ob.S/BS) was the ratio of the ALP-stained area to total bone area and the osteoclast surface/bone surface (Oc.S/BS) was the ratio of the TRAP-stained area to the total bone area [ 43 ], which were quantified using Imagej software.…”
Section: Methodsmentioning
confidence: 99%
“…Bone morphogenetic proteins (BMPs) is a serial of factors belong to TGF-β super-family, and several member of BMP possess excellent potential to commit progenitor cells to osteoblastic lineage, such as BMP2, BMP7 and BMP9 (2,3). To date, expanding evidences support that BMP9 is one of most effective factors to induce osteoblastic commitment, and may be a potent alternative for bone tissue engineering (4,5). However, adipocytes are also presented in the bone masses induced by BMP9 obviously (6).…”
Section: Introductionmentioning
confidence: 99%